2022
DOI: 10.17583/qre.10578
|View full text |Cite
|
Sign up to set email alerts
|

“You Enjoy Talking about It More than Doing It”: Fake Narratives in Disdainful Relationships

Abstract: Research has found that the coercive dominant discourse (CDD) can have a negative impact on girls’ sexual pleasure. In this vein, a previous study found that girls who described relationships under the CDD as exciting also recognized a lack of sexual pleasure in these. One of the elements underlying this apparent contradiction was an identified mismatch between what the participants had experienced in such relationships, characterized for being disdainful, and what they had told their friends. Nonetheless, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
(66 reference statements)
0
7
0
1
Order By: Relevance
“…Ugliness, linked to disdain, humiliation and lack of consent, is present in these casual relationships, as reported in the article. Similarly, in the examined studies, participants reported a relationship between the likelihood of hooking up and owning a car, with participant women confirming their interest in men with such possession (Pedersen et al, 2017;Torras-Gómez et al, 2022). This perception has been cultivated and perpetuated by predatory capital, compelling certain men to view the acquisition of a car as an economic investment aimed at bolstering their desirability.…”
Section: Beauty and Ugliness In Sex: Where Do Profits Lie?mentioning
confidence: 83%
“…Ugliness, linked to disdain, humiliation and lack of consent, is present in these casual relationships, as reported in the article. Similarly, in the examined studies, participants reported a relationship between the likelihood of hooking up and owning a car, with participant women confirming their interest in men with such possession (Pedersen et al, 2017;Torras-Gómez et al, 2022). This perception has been cultivated and perpetuated by predatory capital, compelling certain men to view the acquisition of a car as an economic investment aimed at bolstering their desirability.…”
Section: Beauty and Ugliness In Sex: Where Do Profits Lie?mentioning
confidence: 83%
“…Eric Kandel [32] stated that simply reading a book can change the anatomy of the brain if we can recall something about the reading afterwards, that is, if we have created a memory. Our results show that the specific scientific evidence read and discussed, which included, among others, the dominant coercive discourse [31], peer group pressure to have disdainful hookups [17], and the characteristics and consequences of disdainful hookups [1], led to Simonetta's recollection of new semantic and emotional details of the episode that were related to what had been read and discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Such discourse presents men who have aggressive attitudes and behaviors as most sexually attractive [1]. Studies have shown that such men are preferred for hookups more than for stable relationships [17]. The coercive dominant discourse is boosted and reproduced in interactions in the peer group [17], with some female friends pushing others to engage in such kinds of hookups, presenting them as "cool", while sexual-affective relationships that are egalitarian are presented as boring.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations